2006
DOI: 10.1089/ten.2006.12.2875
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cells Enhance Angiogenesis in Mechanically Viable Prevascularized Tissues via Early Matrix Metalloproteinase Upregulation

Abstract: Angiogenesis, the sprouting of new blood vessels from existing vasculature, is a complex biological process of interest to both the treatment of numerous pathologies and the creation of thick engineered tissues. In the context of tissue engineering, one potential solution to the diffusion limitation is to create a vascular network in vitro that can subsequently anastomose with the host after implantation, allowing the implantation of thicker, more complex tissues. In this study, the ability of endothelial cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 201 publications
(174 citation statements)
references
References 34 publications
(48 reference statements)
14
160
0
Order By: Relevance
“…Interestingly, recent studies have demonstrated that cell adhesion, cytoskeletal organization, and mobility are distinct within the confines of the threedimensional extracellular matrix versus two-dimensional environment (53,54). As such, the new techniques described herein should prove useful for eventually extending these analyses into the more complex third dimension (55,56).…”
Section: Discussionmentioning
confidence: 90%
“…Interestingly, recent studies have demonstrated that cell adhesion, cytoskeletal organization, and mobility are distinct within the confines of the threedimensional extracellular matrix versus two-dimensional environment (53,54). As such, the new techniques described herein should prove useful for eventually extending these analyses into the more complex third dimension (55,56).…”
Section: Discussionmentioning
confidence: 90%
“…Endothelial-coated surface and extracellular matrix (ECM) proteins played a critical role in this early development of EC sprouting 6,13,15 . However, signals from growth factors or mural cells are necessary to maintain and promote the EC sprouting 14,17,38,39 . In our proposed vascular tissue model with capillary network, large number of NHLFs secret signaling molecules ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the fibrinogen concentration reduces the porosity, while increasing the density and stiffness of the fibrin matrix. Although increasing the matrix density increases the number of cell-matrix binding sites, the decrease of porosity and enhanced stiffness are dominant leading to reduced angiogenesis [61].…”
Section: Fibrinmentioning
confidence: 99%